2014
DOI: 10.2147/jbm.s67912
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human T-lymphotropic virus antibodies among patients with lymphoid malignancies at a tertiary center in Lagos, Nigeria

Abstract: BackgroundThere is a significant association of human T-lymphotropic viruses (HTLV) with lymphoid malignancies. HTLV causes a lymphoproliferative malignancy of CD4-activated cells called adult T-cell leukemia/lymphoma (ATL) and a chronic myelopathy called tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM). This study aims to determine the prevalence of HTLV among patients with lymphoid malignancies at a tertiary center in Lagos.MethodsA cross-sectional study was carried out at the hematology c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Furthermore, the findings from this review also show the predominance of infected males as against females widely reported elsewhere. This is consistent with epidemiological studies that show the prevalence of HTLV to vary along sex and reported a higher infection rate in African men or men of African descent [ 39 - 41 ]. This could suggest an etiological factor such as perinatal infectivity as against the transfusion transmission route.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the findings from this review also show the predominance of infected males as against females widely reported elsewhere. This is consistent with epidemiological studies that show the prevalence of HTLV to vary along sex and reported a higher infection rate in African men or men of African descent [ 39 - 41 ]. This could suggest an etiological factor such as perinatal infectivity as against the transfusion transmission route.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical etiological implications of where HTLV-1 infection will be a necessary diagnostic criterion remain largely unclear. Characterized neurological syndromes in the tropics have been classified as tropical myeloneuropathies and grouped into tropical ataxic neuropathy or TSP [ 39 ]. However, our brief review of the literature shows the involvement of HTLV-1 infection although the route of transmission could not be verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation